Influence of role overload and self efficacy on work performance mediated by work engagement and moderate by perceived organizational support - Alexandra Vanessa Gunawan; Ardi Ardi; Dewi Sri Surya Wuisan (Jurnal Mantik, 2024)
The purpose of this study was to determine the effect of role overload and self-efficacy on work performance which is mediated by work engagement and moderated by perceived organizational support. Data collection was carried out using total sampling of all staff working at the RSGMP X by distributing a questionnaire containing 36 questions with a Likert Scale of 1 – 5, then the data was analyzed using the PLS-SEM method. The results of this study state that role overload has a negative influence on work engagement and work performance, while self-efficacy has a positive influence on work engagement and work performance. Work engagement can mediate the influence of role overload and self-efficacy on work performance, but the role of perceived organizational support as moderation does not have a significant influence on the relationship between role overload and work performance